Excellent rate capability and cycle life of Li metal batteries with ZrO2/POSS multilayer-assembled PE separators. (October 2016) - Chi, Mingming; Shi, Liyi; Wang, Zhuyi; Zhu, Jiefang; Mao, Xufeng; Zhao, Yin; Zhang, Meihong; Sun, Lining; Yuan, Shuai
Abstract: Today there are new interests in using metallic lithium as anode materials in lithium batteries because of its extremely large theoretical specific capacity. However, the low cycle efficiency and the lithium dendrite formation during repeated charge/discharge cycles hinder the practical application of metallic lithium anodes. Herein, we report a distinctive ZrO2 /POSS multilayer deposited on PE separators by a simple layer-by-layer (LbL) self-assembly process to enable excellent rate capability and cycle life of lithium metal batteries. The ZrO2 /POSS multilayer on PE separators weakens the solvation effect of lithium ions and significantly enhances the electrolyte uptake of separators, which is responsible for the enhanced ionic conductivity and Li + transference number, as well as the improved Li/electrolyte interfacial stability. These advantageous characteristics of the resulting PE separators effectively decrease the electrode polarization and protect lithium metal anodes against lithium dendrites formation during repeated charge/discharge cycles, endowing LiCoO2 /Li unit cells with both excellent electrochemical performance and high safety. The fundamental understanding on the effects of the micro/nano structures and properties of separators on the important electrochemistry processes at electrode/electrolyte interface of battery systems may lead to new approaches to tackle the intrinsic problems of Li metal anodes for energy storage applications. Graphical abstract: Highlights: An unique ZrO2/POSS layer enables excellent rate capability and cycle life of Li metal batteries. New perspective was provided to tackle the intrinsic problems of Li metal anodes. Deep insights into the role of separators in the whole cell device was given.